IMPLEMENTASI WIRELESS APPLICATION PROTOCOL (WAP) UNTUK LAYANAN PENGISIAN KRS DI POLITAMA SURAKARTA - , Agus Haryawan, ST ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Course registration is a routine activity that is carried out every new semester. For a relatively small number of students, the computer in laboratory is sufficient to complete the activity using the intranet course registration system available now. Along with the increasing number of students in Politama, this computer and intranet system are no longer able to provide students for completing their registration activity. Internet and WAP-based course registration system are developed to overcome this problem. This system provides a choice for students on registering courses via WAP mobile devices. This system is developed with waterfall process model. System analysis and design uses object-oriented method an MVC (Model View Controller) design pattern with UML (Unified Modelling Language) notation. Using this method, this system is expected to be maintainable, easy to develop to the complex system, and easy to integrate with the other academic information system in Politama. System is directly tested with usability testing. There are five usability attribute to be tested, namely learnability, efficiency, memorability, errors, and satisfaction. Results show that this WAP-based system has good enough attribute values. All mean values are above 3 (Easy), based on Likert scale 1 to 4.